2012
DOI: 10.1039/c2dt30121k
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the biomolecular interactions of nickel(ii) hydrazone complexes upon tuning the hydrazide fragment

Abstract: 3 )] (6). Structural characterization of these compounds 4-6 were accomplished by using various physico-chemical techniques. Single crystal X-ray diffraction data of complexes 4 and 5 proved their distorted square planar geometry. In order to ascertain the potential of the above synthesised compounds towards biomolecular interactions, additional experiments involving interaction with calf thymus DNA (CT DNA) and bovine serum albumin (BSA) were carried out. All the ligands and corresponding nickel(II) chelates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 62 publications
3
65
0
Order By: Relevance
“…[17,18] In the spectra of 2, 4, and 5, which contain anionic chelate ligands, the band at ν ≈ 1300 cm -1 corresponds to the ν(C-O) vibration. [10,19] The deprotonation of the hydrazine nitrogen atom results in the formation of an azine group, ϾC=N-N=CϽ, which is manifested in the IR spectra of the complexes by the appearance of bands in the ν = 1613-1585 cm -1 range and the band at ν ≈ 1480 cm -1 . [19,20] The coordination of the pyridine nitrogen atom is indicated by a positive shift (ca.…”
Section: Synthesis and Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…[17,18] In the spectra of 2, 4, and 5, which contain anionic chelate ligands, the band at ν ≈ 1300 cm -1 corresponds to the ν(C-O) vibration. [10,19] The deprotonation of the hydrazine nitrogen atom results in the formation of an azine group, ϾC=N-N=CϽ, which is manifested in the IR spectra of the complexes by the appearance of bands in the ν = 1613-1585 cm -1 range and the band at ν ≈ 1480 cm -1 . [19,20] The coordination of the pyridine nitrogen atom is indicated by a positive shift (ca.…”
Section: Synthesis and Spectroscopymentioning
confidence: 99%
“…Reaction mixtures (1 mL in 40 mm hydrogen carbonate buffer, pH 8.4) consisting of different concentrations of compounds (10,20, and 30 μm) and CT-DNA (138.6 μm) were incubated at 37°C for 60 min with occasional vortexing. The UV/Vis spectra were recorded with a Shimadzu UV-1800 UV/Vis spectrometer operating from λ = 200 to 800 nm with samples in 1.0 cm quartz cells.…”
Section: Dna Binding Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these compounds show remarkable biological activities which are greatly related to their metal complexation ability [6].…”
mentioning
confidence: 99%
“…The observed red or blue shift revealed the interaction between the complexes and BSA at hydrophobic sites. [49] The fluorescence quenching constant (K q ) values were found by Stern-Volmer equation using of n (~1) strongly reinforced the presence of a single binding site in BSA. The values of K b suggested that complex 1 interacted with BSA rather strongly relative to the other complexes.…”
Section: Fluorescence Spectramentioning
confidence: 99%